2018
DOI: 10.1038/s41386-018-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic functional connectivity correlates of person-level risk for bipolar disorder in offspring of affected parents

Abstract: Offspring of parents with bipolar disorder (OBP) are at increased risk to develop bipolar disorder (BD). Alterations in resting-state functional connectivity (rsFC) have been identified in OBP; however, replication has been limited and correlation with person-level risk is unknown. A recent study found reduced rsFC between left inferior frontal gyrus (IFG) and clusters in the left insula (LINS), lentiform nucleus (LENT), and midcingulate cortex (MCING) in OBP (Roberts et al. 2017); here, we aim to extend these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Based on their known structural and functional properties, networks included the default mode (DMN), posterior DMN, salience (SN), left and right executive control (lECN and rECN, respectively), language (LN), and anterior DMN (aDMN) (for regional anatomical labels and spatial correlates, see Supplement 1, available online). These components were spatially correlated with individual network functional region-of-interest atlases, and were similar to those observed in published ICA analyses in the BD literature13,15,22 and referenced brain network templates 43.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Based on their known structural and functional properties, networks included the default mode (DMN), posterior DMN, salience (SN), left and right executive control (lECN and rECN, respectively), language (LN), and anterior DMN (aDMN) (for regional anatomical labels and spatial correlates, see Supplement 1, available online). These components were spatially correlated with individual network functional region-of-interest atlases, and were similar to those observed in published ICA analyses in the BD literature13,15,22 and referenced brain network templates 43.…”
supporting
confidence: 81%
“…To date, no study has examined changes in intrinsic functional connectivity in youths with a familial vulnerability for BD who receive a psychosocial intervention. Drawing on findings from resting state functional magnetic resonance imaging (fMRI) in youths at risk for BD, 6,13,22 we predicted that, compared with healthy offspring of parents with no history of any psychiatric disorders, youth offspring of parents with BD would show patterns of reduced intrinsic functional connectivity between the VLPFC, ECN, and DMN networks. In addition, we hypothesized that over 4 months of intervention, FFT-HR would increase prefrontalÀlimbic connectivity to baseline levels observed in HC youths to a greater extent than EC.…”
mentioning
confidence: 99%
“…For all subjects, we calculated a quality control measure with respect to head motion, namely volume-to-volume frame displacement (FD). Consistent with recent developmental cognitive neuroscience publications (Bathelt, Johnson, Zhang, & Astle, 2019;Calabro et al, 2019;Hafeman et al, 2019;Li et al, 2019), subjects were removed from rsfMRI analyses if the average frame displacement across the run was >0.5 mm (N = 5). Note: Detailed exclusion criteria are provided in Figure S1.…”
Section: Rsfmri Processingmentioning
confidence: 99%
“…Task-based functional magnetic resonance imaging (fMRI) studies have shown enhanced regional functional activation following mindfulness practice in the dorsolateral PFC, medial PFC, ACC and insula [ 10 ], which are hub regions of the DMN, FPN and CON. Moreover, previous studies have also found that individuals at high familial risk for BD exhibited functional abnormalities in these regions and networks [ 17 19 ]. MBCT-C may therefore enhance the function of these networks and further facilitate these processes to accomplish therapeutic effects on mood dysregulated adolescents at familial risk for BD.…”
Section: Introductionmentioning
confidence: 99%